Secular translations: nation-state, modern self, and calculative reason - Asad, Talal (Ruth Benedict Book Series, 2018)
In Secular Translations, anthropologist Talal Asad reflects on his lifelong engagement with secularism and its contradictions. He draws out the ambiguities in our concepts of the religious and the secular through a rich consideration of translatability and untranslatability